Immature stages of three Japanese species of the genus Plecia Wiedemann (Diptera: Bibionidae) - Sutou, Mitsuaki (Zootaxa, 2006)
The eggs, larvae, and pupae (male and female) of three Japanese species of the Bibionidae, Plecia adiastola, P. membranifera, and P. hadrosoma, are described and illustrated, and ecological notes are included. Morphological characters of the immature stages of Plecia species are compared for the first time, and a diagnosis is presented. The taxonomic and phylogenetic importance of morphological characters, especially of the larval head and the arrangement of the larval and pupal body processes, is discussed.